PENGARUH PEMBELAJARAN BERBASIS LABORATORIUM TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA - Elka Ayu Setianingsih; Arwin Achmad; Rini RitaT Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
The purpose of this study is to determine the effect of the  laboratory-based learning toward   student  activitites and learning outcomes. The research  used  a pretest-posttest design. The samples in this study were student of class VIIIA and VIIIB   that  were randomly selected using cluster random sampling technique. The study collected quantitative data and qualitative data. Quantitative data  of  student learning outcomes obtained from pre test and posttest. Quantitative data  was analyzed using t-test at 5% confidence level. Qualitative data was  student activity  observed during laboratory-based learning.The results of this study showed that the  N-gain score of student  of experimental  class which using  laboratory-based learning was 60.51  higher than the average  N-gain  score of student of control class which  using discussion learning (49.71). Furthermore, the N-gain score of students' learning activities  of the experimental class reached 77.4 was higher than the control class that was 70.4. It can be concluded that the use of laboratory-based learning could improved student activities and learning outcomes of human digestive system concepts. Keywords: Lab-Based Learning, Student Activities, Learning Outcomes, Digestive System.